Stimulasi Motorik Halus Anak Usia Dini Melalui Media Pohon Pintar dalam Mengenal Lambang Bilangan - Kendri Kendri; Ezif Rizqi (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This study aims to describe the stimulation of fine motor skills in early childhood through the use of the “Smart Tree” (Pohon Pintar) media in recognizing number symbols among children aged 4–5 years at Pelangi Playgroup. This research employs a qualitative approach with a descriptive research design. The subjects of the study consist of 17 children. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted through data reduction, data display, and conclusion drawing. The results of the study indicate that the use of the Smart Tree media is able to improve children's fine motor skills, such as pinching, sticking, and coordinating hand and eye movements. In addition, children’s ability to recognize number symbols also shows improvement through concrete and enjoyable activities. This media is proven to be effective in creating interactive and meaningful learning experiences.